Leveraging Waiterio as Learning Media for English for Restaurant: A Case Study - Komang Satya Permadi; Nyoman Canestra Adi Putra; Ni Wayan Putri Widia Artayani (General English Education, 2025)
This research investigates rationale, implementation, and pedagogical implications of employing the Waiterio application as a learning media within an English for Restaurant. Employing a purposive sampling methodology, the study involved twenty-six students and one instructor. Data collection was conducted through a case study approach, utilizing observational methods, literature review, interviews, and questionnaires. Qualitative data analysis was employed to interpret the findings. The study revealed that Waiterio application is favored due to its user-friendly interface in comparison to alternative applications. Furthermore, its high degree of flexibility, facilitated by its accessibility across multiple platforms, makes it particularly suitable for diverse learning environments. The research indicated that Waiterio application can be readily integrated into the English for Restaurant curriculum, particularly in facilitating learning related to service sequences. However, limitations were identified, including the requirement for a stable internet connection and the absence of reservation feature. Despite these limitations, student participants unanimously acknowledged the application's ease of use and strongly recommended its utilization within the Food and Beverage Service department. The study concluded that the Waiterio application, owing to its user-friendly interface, can serve as a foundational tool for introducing students to Point of Service applications before transitioning to more comprehensive and complex platforms.